INTEGRASI AWAN TITIK DARI PEMINDAI LASER TERESTRIS DAN FOTOGRAMETRI UNTUK BERBAGAI KEDETILAN OBJEK STUDI KASUS: CANDI SARI - Eka Wicaksono, Darmawan
Integration is an activity to combine two or more data with different characteristics of 3D models, to produce a 3D model with the best results. The discussion in this study includes the process of acquisition, processing, and analysis of the geometric quality from the results of TLS processing; starting with the registration process to georeferencing, as well as photogrammetric processing such as image matching process to produce two point clouds that are ready to be integrated. The final result of the integration of the two point clouds is the 3D point cloud model that has become a single entity with differences in the detailed relief areas that have improved texture geometric qualities. The result does not experience differences far enough before the integration process. The object to be used as an object of research in this study is Sari Temple, located in Bantul Regency, Special Region of Yogyakarta, Indonesia.